Development and implementation of the Ebola Exposure Window Calculator: A tool for Ebola virus disease outbreak field investigations. - Amy Whitesell; Nirma D Bustamante; Miles Stewart; Jeff Freeman; Amber M Dismer; Walter Alarcon; Aaron Kofman; Amen Ben Hamida; Stuart T Nichol; Inger Damon; Dana L Haberling; Mory Keita; et al. (PLoS ONE)
During an Ebola virus disease (EVD) outbreak, calculating the exposure window of a confirmed case can assist field investigators in identifying the source of infection and establishing chains of transmission. However, field investigators often have difficulty calculating this window. We developed a bilingual (English/French), smartphone-based field application to assist field investigators in determining the exposure window of an EVD case. The calculator only requires the reported date of symptoms onset and the type of symptoms present at onset or the date of death. Prior to the release of this application, there was no similar electronic capability to enable consistent calculation of EVD exposure windows for field investigators. The Democratic Republic of the Congo Ministry of Health endorsed the application and incorporated it into trainings for field staff. Available for Apple and Android devices, the calculator continues to be downloaded even as the eastern DRC outbreak resolved. We rapidly developed and implemented a smartphone application to estimate the exposure window for EVD cases in an outbreak setting.